Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41392-020-00438-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) membrane (M) protein inhibits type I and III interferon production by targeting RIG-I/MDA-5 signaling

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has quickly spread worldwide and has affected more than 10 million individuals. A typical feature of COVID-19 is the suppression of type I and III interferon (IFN)-mediated antiviral immunity. However, the molecular mechanism by which SARS-CoV-2 evades antiviral immunity remains elusive. Here, we reported that the SARS-CoV-2 membrane (M) protein inhibits the production of type I and III IFNs induced by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
218
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(235 citation statements)
references
References 48 publications
0
218
0
1
Order By: Relevance
“…It showed that N protein mainly involved in viral mRNA transcription and replication and cytoskeletal and immune regulation of host cells [58] . The M protein of SARS-CoV-2 can inhibit IFN-β promoter activation and participate in evading host anti-viral immunity [59] . E protein relates to the virus pathogenicity and may activate the host's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…It showed that N protein mainly involved in viral mRNA transcription and replication and cytoskeletal and immune regulation of host cells [58] . The M protein of SARS-CoV-2 can inhibit IFN-β promoter activation and participate in evading host anti-viral immunity [59] . E protein relates to the virus pathogenicity and may activate the host's inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Membrane (M) protein inhibits type I and III IFN production by targeting RIG-I/MDA-5. 53 ORF6 is shown to inhibit both type I IFN production and downstream signaling. 54 , 55 Despite most of the recent identified SARS-CoV-2 viral proteins are shown to restrict host immune response, which is regarded as a common defense strategy that pathogenic viruses use to replicate and propagate in their host, our study revealed the SARS-CoV-2 N protein could positively regulate inflammatory responses through promoting NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…The envelope (E) protein likely forms a viroporin, which is important for virus assembly and release, and is also a putative virulence determinant [ 23 ]. The membrane (M) protein is an abundantly expressed structural protein within the lipid envelope that is also important for viral morphogenesis and interferon suppression [ 24 ]. Finally, the nucleocapsid protein (N) stabilizes the RNA genome in a helical complex [ 25 ] and serves as a key target of adaptive immunity.…”
Section: Taxonomy Genomic Organization and Replication Cycle Of Sarmentioning
confidence: 99%